"The Most Disastrous and Fatal Epidemic": Mortality Statistics During the 1890 Russian Influenza Epidemic in Connecticut. (January 2022) - Ewing, E. Thomas
During the Russian influenza pandemic, which reached the United States in late 1889, US public health officials attempted to document the number of deaths associated with this disease outbreak. A historical perspective illuminates the complex categories used to classify deaths from influenza-associated diseases; substantial changes in weekly, monthly, and yearly death totals; and thoughtful efforts by health officials to measure the epidemic as it happened. The 1114 influenza deaths reported by the Connecticut State Board of Health in the 3 years after the January 1890 outbreak must be supplemented by the notable increases in the number of deaths from respiratory diseases, which elevates the likely toll to more than 7000 deaths during the epidemic. Whereas historians of public health have primarily examined efforts to control communicable diseases, this case study of mortality statistics reported by town officials and analyzed by the Connecticut State Board of Health demonstrates how officers of the local boards of health also responded to unexpected outbreaks of a familiar disease such as influenza. Understanding how organizations measured influenza-associated mortality illustrates an important stage in the development of American public health and also makes an important contribution to studying pandemics in history.